Preparation method of nano calcium carbonate for gas-phase antirust master batch
Nano calcium carbonate carrier with mesoporous-macroporous structure was synthesized by the biological template method, and the pH-sensitive film layer was coated on its surface, which solved the problem of excessively fast release rate of corrosion inhibitors in the prior art, and achieved a long-term anti-rust effect on metal surfaces.
Patent Information
- Application Number
- CN202510307360.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-17
AI Technical Summary
The initial release rate of existing nano calcium carbonate anti-rust agents in solvent environments is too fast to achieve long-term protection.
The carrier with a mesoporous-macroporous structure was synthesized by the biological template method, directed growth of nano calcium carbonate, and coated with a pH-sensitive film layer on its surface to achieve phased controlled release of the corrosion inhibitor.
It realizes dynamic rust prevention on metal surfaces, and the corrosion inhibitor is dissolved and released in an acidic environment, which significantly improves the long-term effectiveness of the rust prevention effect.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano calcium carbonate, in particular to a method for preparing nano calcium carbonate for gas phase antirust masterbatch. Background Art
[0002] As an important filler, nano calcium carbonate is widely used in industries such as plastics, papermaking, sealants, and coatings. Nano calcium carbonate has a small particle size and can better penetrate into gaps and form a strong bond with the surface of various materials.
[0003] The Chinese invention patent with publication number CN106277011B discloses a nano calcium carbonate concentrated slurry and a preparation method thereof. The concentrated slurry consists of 100 parts of nano calcium carbonate, 5 to 10 parts of an organic corrosion inhibitor, 0.1 to 0.3 parts of an anti-rust pigment, 0.3 to 0.6 parts of an additive, and 15 to 20 parts of an organic solvent; each component is weighed in proportion, and the organic corrosion inhibitor, the anti-rust pigment, the additive and the organic solvent are uniformly mixed; nano calcium carbonate powder is gradually added during the continuous rotation of a high-speed disperser, and after all the required nano calcium carbonate powder is added, the dispersion is continued for 5 to 30 minutes, and the speed of the disperser is 1500 to 2500 rpm; the obtained nano calcium carbonate slurry is ground in a ball mill or a sand mill for 1 to 10 hours to make its average particle size below 100 nanometers to obtain a nano calcium carbonate concentrated slurry.
[0004] In the above scheme, components such as organic corrosion inhibitors and organic corrosion inhibitors are dispersed in the nano-calcium carbonate concentrated slurry. The corrosion inhibitors are directly exposed to the solvent environment, and the initial release rate is too fast to achieve long-term protection. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a method for preparing nano calcium carbonate for gas phase anti-rust masterbatch, aiming to realize the staged controlled release of corrosion inhibitor. Specifically, it is achieved through the following technical solutions: A method for preparing nano calcium carbonate for gas phase antirust masterbatch comprises the following steps: S1, corn starch and deionized water are mixed in a mass ratio of (3-8):40, dispersed evenly to form a suspension, heated to 70-80°C for gelatinization to obtain a translucent gel; S2, adding 0.5% to 1% of the mass of a crystal form control agent to a CaCl2 solution having a mass concentration of 20% to 45% to obtain a loaded mixed solution; S3, immersing the translucent gel in the loading mixed solution, taking it out and freeze-drying it to obtain a starch template with directional pores; S4, laying the starch template on the bed layer of the fixed bed reactor, maintaining the temperature at 25±1°C, introducing CO2 from the bottom at a flow rate of 0.5-0.8L / min for carbonization reaction, and when the pH of the system measured at the pH monitoring point drops to 8.2, stop introducing CO2 to obtain a carbonized product; S5, enzymatically treating the carbonized product to degrade the starch template, centrifugally washing the enzymatic product with a washing liquid, collecting the solid matter, and vacuum drying to obtain needle-shaped nano-calcium carbonate; S6. Dissolve the corrosion inhibitor in ethanol to prepare a corrosion inhibitor solution with a mass concentration of 1% to 5%, immerse the nano-calcium carbonate in the corrosion inhibitor solution at a mass ratio of (1 to 4): 10, evacuate to 0.01 to 0.05 MPa, maintain for 1 to 1.5 hours, centrifuge to remove excess solution, and vacuum dry to obtain nano-calcium carbonate loaded with corrosion inhibitor; S7. Coating a pH sensitive film layer on the outer surface of the nano calcium carbonate loaded with corrosion inhibitor to obtain a nano calcium carbonate product.
[0006] Preferably, in step S7, chitosan is first dissolved in an acetic acid solution with a mass concentration of 1% to prepare a chitosan solution with a mass concentration of 1% to 5%, and then the nano-calcium carbonate loaded with a corrosion inhibitor is immersed in the chitosan solution at a mass ratio of (1 to 3): 1, and a cross-linking agent accounting for 0.1% to 0.5% of the total mass of the chitosan solution is added, stirred for 6 to 8 hours, taken out and centrifuged to remove excess solution, and vacuum dried to obtain a nano-calcium carbonate product.
[0007] Preferably, the cross-linking agent is glutaraldehyde.
[0008] Preferably, in step S3, the surface of the starch template is firstly rapidly frozen with liquid nitrogen to form macropores, and then the interior of the starch template is slowly frozen at -40°C to form mesopores, thereby constructing a gradient pore structure of the starch template.
[0009] Preferably, in step S5, the carbonized product is first immersed in an α-amylase solution for enzymolysis for 3.5 to 5 hours, maintaining a temperature of 50 to 60° C., and then centrifuged using an ethanol solution with a mass concentration of 75% as a washing liquid to remove residual enzymes and sugars.
[0010] Preferably, the mass ratio of the α-amylase solution to the carbonized product is 1:(3-5), and the mass concentration of the α-amylase solution is 1%-5%.
[0011] Preferably, the corrosion inhibitor is prepared by compounding benzotriazole and capric acid in a mass ratio of 3:1.
[0012] Preferably, the crystal form controlling agent is polyacrylic acid.
[0013] After adopting the above technical solution, the beneficial effects of the present invention are: The present invention utilizes a biological template method to synthesize a carrier with a mesoporous-macroporous structure, guides the directional growth of nano-calcium carbonate, and the pH-sensitive film layer coated with the nano-calcium carbonate dissolves and releases a corrosion inhibitor in an acidic environment, thereby achieving dynamic rust prevention on the metal surface. DETAILED DESCRIPTION
[0014] The features and exemplary embodiments of various aspects of the present invention will be described in detail below. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present invention by illustrating examples of the present invention.
[0015] Example 1 In this specific embodiment, the invention provides a method for preparing nano calcium carbonate for gas phase antirust masterbatch, which achieves high efficiency and long-term performance of nano calcium carbonate-based gas phase antirust masterbatch.
[0016] S1: Preparation of translucent gel Corn starch and deionized water were mixed in a mass ratio of 3:40, stirred thoroughly, and prepared into a uniform suspension. The temperature was raised to 70°C for gelatinization, and the temperature was maintained for 15 minutes with continuous stirring to obtain a translucent gel. Stirring can ensure that the starch particles are evenly dispersed and prevent agglomeration. The stirring shear force promotes the full expansion and rupture of the starch particles. The three-dimensional gel network and pore structure formed after the gelatinization of corn starch provide spatial constraints and directional channels for the nucleation and growth of calcium carbonate. Cool naturally to room temperature to form a uniform porous base.
[0017] S2: Preparation of loading mixture 0.5% polyacrylic acid was added to a CaCl2 solution with a mass concentration of 20%, and the mixed solution was ultrasonically treated for 10 minutes to ensure that the polyacrylic acid was fully dispersed to prepare a uniform loaded mixed solution.
[0018] The three-dimensional gel network formed after corn starch gelatinization adsorbs calcium ions through hydrogen bonds and electrostatic effects. Due to the coordination effect between the hydroxyl groups on the starch molecular chains and the calcium ions, calcium ions are preferentially enriched in the pores of the starch template, forming local high-concentration areas, restricting the free growth of calcium carbonate crystals and guiding them to extend into needles along the axial direction of the pores.
[0019] As a crystal control agent, polyacrylic acid can directionally inhibit the growth rate of specific crystal faces of calcium carbonate through chemical adsorption and chelation, thereby promoting the formation of needle-shaped nano-calcium carbonate.
[0020] S3: Gradient pore construction At 20°C, immerse the translucent gel in the loading mixed solution, with the liquid level 1 cm above the top of the translucent gel to ensure complete immersion. Maintain a negative pressure of -0.08MPa, circulate the loading mixed solution with a peristaltic pump, and immerse for 20 minutes. After immersion, remove the translucent gel to obtain the loading gel.
[0021] Use a liquid nitrogen spray gun to evenly spray the surface of the loaded gel for 15 to 30 seconds. This process will rapidly reduce the temperature of the loaded gel, causing water molecules to quickly freeze inside the gel to form ice crystals. The rapid growth of ice crystals will build large pores on the loaded gel.
[0022] The loaded gel was then transferred to a freeze dryer and pre-frozen at -40°C for 3 hours to ensure that all water molecules inside the loaded gel formed ice crystals and to construct mesopores on the loaded gel. After pre-freezing, the vacuum degree was regulated to ≤10Pa, and the temperature was first raised to 0°C to allow the ice crystals to sublime directly, and then raised to 20°C for analytical drying to finally obtain a starch template with a gradient pore structure.
[0023] S4, carbonization reaction Immerse the starch template in a 0.2mol / L NH3·H2O solution, with the liquid level 1cm above the top of the starch template, ensuring complete immersion, maintaining a negative pressure of -0.08MPa, and immerse for 5min. Take out the starch template, spread it flat on the porous bed of the fixed bed reactor, maintain the temperature at 25°C, and introduce CO2 from the bottom at a flow rate of 0.5L / min for carbonization reaction. When the pH monitoring point measures that the pH of the system drops to 8.2, stop introducing CO2, terminate the reaction, and obtain a carbonized product.
[0024] The gradient distribution of macropores and mesopores in the starch template optimizes the mass transfer path and improves the diffusion efficiency of CO2. NH3·H2O provides an alkaline environment, and the carbonate generated by CO2 reacts with calcium ions to form calcium carbonate precipitation. The hydroxyl groups of the starch template coordinate with calcium ions, enriching calcium ions in the pores, restricting the diffusion of carbonate, and promoting the growth of calcium carbonate along the axial direction of the pores. Polyacrylic acid directionally regulates the crystal growth direction, and finally forms nano calcium carbonate with a needle-like morphology.
[0025] When this needle-shaped nano calcium carbonate is made into a vapor phase anti-rust masterbatch with other raw materials and applied to metal packaging, its unique needle-shaped structure can form a fiber-like stress transfer network in the composite material. This network structure not only enhances the overall strength of the composite material and improves its pressure bearing capacity (such as the stacking pressure of metal, reduces creep deformation under long-term stress, and prolongs the service life of metal packaging), but also significantly improves the impact resistance of the composite material, so that it can better protect the metal packaging from damage during transportation and storage.
[0026] S5: Enzymatic hydrolysis and washing The carbonized product was immersed in a 1% α-amylase solution, the mass ratio of the α-amylase solution to the carbonized product was 1:3, the temperature was maintained at 50°C, and the enzymolysis was performed for 5 hours. α-amylase hydrolyzed starch to release nano-calcium carbonate. An ethanol solution with a mass concentration of 75% was used as a washing liquid to centrifuge and wash the enzymolysis product to remove residual enzymes and sugars. The solid matter was collected and vacuum dried to obtain needle-shaped nano-calcium carbonate.
[0027] S6: Corrosion Inhibitor Loading Benzotriazole and decanoic acid are compounded into a corrosion inhibitor at a mass ratio of 3:1, and the corrosion inhibitor is dissolved in ethanol to prepare a corrosion inhibitor solution with a mass concentration of 1%. At a mass ratio of 1:10, the nano-calcium carbonate obtained in step 5 is immersed in the corrosion inhibitor solution, and vacuumed to 0.01MPa, maintained for 1h, to ensure that the corrosion inhibitor is fully adsorbed to the nano-calcium carbonate. Then, the excess solution is removed by centrifugation, and vacuum drying is performed to obtain the nano-calcium carbonate loaded with the corrosion inhibitor.
[0028] S7: pH sensitive membrane coating Chitosan was dissolved in acetic acid solution with a mass concentration of 1% to prepare chitosan solution with a mass concentration of 1%. Nano calcium carbonate loaded with corrosion inhibitor was immersed in the chitosan solution at a mass ratio of 1:1, glutaraldehyde accounting for 0.1% of the total mass of the chitosan solution was added, and stirred for 6 hours. After being taken out, it was centrifuged and washed with sodium cyanoborohydride solution with a mass concentration of 0.2%, and then centrifuged and washed twice with deionized water, and vacuum dried to obtain nano calcium carbonate products.
[0029] Chitosan is adsorbed on the surface of nano-calcium carbonate through electrostatic action to form a uniform film layer. Glutaraldehyde reacts with the amino groups in the chitosan molecules to form a three-dimensional cross-linked structure, which enhances the mechanical strength of the film layer. Sodium cyanoborohydride reduces the unreacted glutaraldehyde aldehyde group and the unstable Schiff base intermediate to a stable amine group, eliminating toxicity and improving the stability of the film layer. The cross-linking reaction of glutaraldehyde consumes part of its hydrophilic amino group. The introduction of hydrophobic segments can reduce the hydration capacity of the film layer and inhibit swelling. When the local environmental pH decreases (such as the acidic environment caused by metal corrosion), the amino groups in the chitosan film are further protonated, the film layer swells and ruptures, and the corrosion inhibitor is released from the nano-calcium carbonate.
[0030] Example 2 S1 adjustment: corn starch and deionized water are mixed in a mass ratio of 5:40, and the temperature is raised to 72° C. for gelatinization to obtain a translucent gel.
[0031] S2 adjustment: add 0.8% by weight of polyacrylic acid to a CaCl2 solution with a mass concentration of 25% to prepare a uniform loaded mixed solution.
[0032] S4 adjustment: CO2 is introduced at a flow rate of 0.55 L / min for carbonization reaction. After the reaction is completed, a carbonization product is obtained.
[0033] S5 adjustment: the carbonized product is immersed in a 3% mass concentration α-amylase solution, the mass ratio of the α-amylase solution to the carbonized product is 1:3.5, the temperature is maintained at 55°C, and the enzymolysis is carried out for 3.5 hours to release nano-calcium carbonate. The enzymolysis product is centrifuged and washed with a 75% mass concentration ethanol solution as a washing liquid to obtain needle-shaped nano-calcium carbonate.
[0034] S6 adjustment: dissolve the corrosion inhibitor in ethanol to prepare a corrosion inhibitor solution with a mass concentration of 3.5%, immerse the nano-calcium carbonate in the corrosion inhibitor solution at a mass ratio of 3:10, evacuate to 0.02MPa, maintain for 1.2h, centrifuge to remove excess solution, vacuum dry, and obtain nano-calcium carbonate loaded with corrosion inhibitor.
[0035] S7 adjustment: dissolve chitosan in 1% acetic acid solution to prepare a chitosan solution with a mass concentration of 3%, immerse the nano-calcium carbonate loaded with corrosion inhibitor in the chitosan solution at a mass ratio of 2:1, add glutaraldehyde accounting for 0.3% of the total mass of the chitosan solution, stir for 6.5 hours, take out, centrifuge and wash with 0.25% sodium cyanoborohydride solution, then centrifuge and wash twice with deionized water, and vacuum dry to obtain a nano-calcium carbonate product.
[0036] Example 3 S1 adjustment: corn starch and deionized water are mixed in a mass ratio of 1:5, and the temperature is raised to 80° C. for gelatinization to obtain a translucent gel.
[0037] S2 adjustment: add 1% by mass of polyacrylic acid to a 45% by mass concentration CaCl2 solution to prepare a uniform loaded mixed solution.
[0038] S4 adjustment: CO2 is introduced at a flow rate of 0.8 L / min for carbonization reaction. After the reaction is completed, a carbonization product is obtained.
[0039] S5 adjustment: the carbonized product is immersed in a 5% mass concentration α-amylase solution, the mass ratio of the α-amylase solution to the carbonized product is 1:5, the temperature is maintained at 60°C, and the enzymolysis is performed for 5 hours to release nano-calcium carbonate. An ethanol solution with a mass concentration of 80% is used as a washing liquid to centrifuge and wash the enzymolysis product to obtain needle-shaped nano-calcium carbonate.
[0040] S6 adjustment: dissolve the corrosion inhibitor in ethanol to prepare a corrosion inhibitor solution with a mass concentration of 5%, immerse the nano-calcium carbonate in the corrosion inhibitor solution at a mass ratio of 2:5, evacuate to 0.05MPa, maintain for 1.5h, centrifuge to remove excess solution, vacuum dry, and obtain nano-calcium carbonate loaded with corrosion inhibitor.
[0041] S7 adjustment: dissolve chitosan in 1% acetic acid solution to prepare a chitosan solution with a mass concentration of 5%, immerse the nano-calcium carbonate loaded with corrosion inhibitor in the chitosan solution at a mass ratio of 3:1, add glutaraldehyde accounting for 0.5% of the total mass of the chitosan solution, stir for 8 hours, take out, centrifuge and wash with a sodium cyanoborohydride solution with a mass concentration of 0.5%, then centrifuge and wash twice with deionized water, and vacuum dry to obtain a nano-calcium carbonate product.
[0042] Preparation of VCI gas phase anti-rust masterbatch Benzotriazole, sodium benzoate, hexamethylenetetramine, and phytic acid were mixed uniformly in a mass ratio of 3:5:1:1 to prepare a compound rust inhibitor. The compound rust inhibitor, nano calcium carbonate (derived from Examples 1-3), and polyethylene were mixed in a mass ratio of 2.5:1.5:6, and the mixed raw materials were used to prepare rust-proof masterbatches using a high-speed granulator. According to the material selection of Examples 1-3, the rust-proof masterbatches were respectively recorded as VCI-1, VCI-2, and VCI-3. In addition, the compound rust inhibitor and polyethylene were mixed in a mass ratio of 2.5:6, and the mixed raw materials were used to prepare rust-proof masterbatches using a high-speed granulator, recorded as VCI-4, as a control group.
[0043] Preparation of anti-rust film The prepared four kinds of anti-rust masterbatch were added into polyethylene at a mass fraction of 15%, and the mixture was processed into polyethylene by film blowing. In addition, pure polyethylene was prepared and made into anti-rust film.
[0044] According to GB / T 1040.3-2006, the above five anti-rust films were made into test specimens for tensile and tear strength testing to analyze the mechanical properties of the anti-rust films. The results are shown in Table 1.
[0045] Table 1. Mechanical properties of anti-rust film
[0046] Due to the reinforcing effect and stress dispersion of nano-calcium carbonate, the tensile strength and tear strength of the anti-rust film of VCI-1~3 are significantly higher than those of pure polyethylene and VCI-4. They can better withstand external forces and maintain the integrity of the packaging, thus enhancing the anti-rust effect to a certain extent.
[0047] Ten copper sheets of 15 mm × 40 mm × 1 mm were prepared, of which eight were wrapped with anti-rust film and the remaining two were left unwrapped. Acid salt spray (GB / T 24195-2009; acid salt spray 2 h + drying 4 h + wetting 2 h; 30 cycles) and neutral salt spray tests (GB / T 10125-2012; spray 8 h, stop 16 h; 10 days). The results are shown in Table 2 (percentage of copper sheet corrosion area).
[0048] Table 2. Corrosion resistance of anti-rust film
[0049] Under acidic conditions, the polysaccharide film rapidly protonates and swells, and the corrosion inhibitor is quickly released to form a passivation film to inhibit copper corrosion. Under neutral conditions, the polysaccharide film is stable, and the corrosion inhibitor is slowly released to inhibit alkaline corrosion for a long time.
[0050] According to the embodiments of the present invention as described above, these embodiments do not describe all the details in detail, nor do they limit the invention to specific embodiments. Obviously, many modifications and changes can be made based on the above description. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can make good use of the present invention and the modified use based on the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing nano calcium carbonate for gas phase antirust masterbatch, characterized in that: The steps include: S1, corn starch and deionized water are mixed in a mass ratio of (3-8):40, dispersed evenly to form a suspension, heated to 70-80°C for gelatinization to obtain a translucent gel; S2, adding 0.5% to 1% of the mass of a crystal control agent to a CaCl2 solution having a mass concentration of 20% to 45% to obtain a loaded mixed solution; S3, immersing the translucent gel in the loading mixed solution, taking it out and freeze-drying it to obtain a starch template with directional pores; S4, completely immersing the starch template in NH3·H2O solution, taking it out and spreading it on the bed of the fixed bed reactor, maintaining the temperature at 25±1°C, introducing CO2 from the bottom at a flow rate of 0.5-0.8L / min for carbonization reaction, and stopping the introduction when the pH of the system measured at the pH monitoring point drops to 8.2 to obtain a carbonized product; S5, enzymatically treating the carbonized product to degrade the starch template, centrifugally washing the enzymatic product with a washing liquid, collecting the solid matter, and vacuum drying to obtain needle-shaped nano-calcium carbonate; S6. Dissolve the corrosion inhibitor in ethanol to prepare a corrosion inhibitor solution with a mass concentration of 1% to 5%, immerse the nano-calcium carbonate in the corrosion inhibitor solution at a mass ratio of (1 to 4): 10, evacuate to 0.01 to 0.05 MPa, maintain for 1 to 1.5 hours, centrifuge to remove excess solution, and vacuum dry to obtain nano-calcium carbonate loaded with corrosion inhibitor; S7. Coating a pH sensitive film layer on the outer surface of the nano calcium carbonate loaded with corrosion inhibitor to obtain a nano calcium carbonate product.
2. The method for preparing nano calcium carbonate for gas phase antirust masterbatch according to claim 1, characterized in that: In the step S7, chitosan is first dissolved in an acetic acid solution with a mass concentration of 1% to prepare a chitosan solution with a mass concentration of 1% to 5%, and then the nano-calcium carbonate loaded with a corrosion inhibitor is immersed in the chitosan solution at a mass ratio of (1 to 3):1, and a cross-linking agent accounting for 0.1% to 0.5% of the total mass of the chitosan solution is added, stirred for 6 to 8 hours, taken out and centrifuged to remove excess solution, and vacuum dried to obtain a nano-calcium carbonate product.
3. The method for preparing nano calcium carbonate for gas phase antirust masterbatch according to claim 2, characterized in that: The cross-linking agent is glutaraldehyde.
4. The method for preparing nano calcium carbonate for gas phase antirust masterbatch according to claim 1, characterized in that: In step S3, the surface of the starch template is firstly rapidly frozen by liquid nitrogen to form macropores, and then the interior of the starch template is slowly frozen at -40°C to form mesopores, thereby constructing a gradient pore structure of the starch template.
5. The method for preparing nano calcium carbonate for gas phase antirust masterbatch according to claim 1, characterized in that: In step S5, the carbonized product is first immersed in an α-amylase solution for enzymolysis for 3.5 to 5 hours, and the temperature is maintained at 50 to 60° C., and then centrifuged and washed using an ethanol solution with a mass concentration of 75% as a washing liquid to remove residual enzymes and sugars.
6. The method for preparing nano calcium carbonate for gas phase antirust masterbatch according to claim 5, characterized in that: The mass ratio of the α-amylase solution to the carbonized product is 1:(3-5), and the mass concentration of the α-amylase solution is 1%-5%.
7. The method for preparing nano calcium carbonate for gas phase antirust masterbatch according to claim 1, characterized in that: The corrosion inhibitor is prepared by compounding benzotriazole and capric acid in a mass ratio of 3:
1.
8. The method for preparing nano calcium carbonate for gas phase antirust masterbatch according to claim 1, characterized in that: The crystal form controlling agent is polyacrylic acid.
Citation Information
Patent Citations
A nano calcium carbonate concentrated slurry and its preparation method
CN106277011B
Method for preparing cubic nano calcium carbonate
CN104556185A
Preparation method for fluffy-ball calcium carbonate nano mixed crystal particles
CN108467053A
Spherical calcium carbonate and preparation method thereof
CN109824077A
Preparation method of porous hollow calcium carbonate drug-loaded microspheres
CN111994935A